2011
DOI: 10.1890/10-0709.1
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the drivers of reduced long-distance seed dispersal by birds in an experimentally fragmented landscape

Abstract: Seed dispersal is a crucial component of plant population dynamics. Human landscape modifications, such as habitat destruction and fragmentation, can alter the abundance of fruiting plants and animal dispersers, foraging rates, vector movement, and the composition of the disperser community, all of which can singly or in concert affect seed dispersal. Here, we quantify and tease apart the effects of landscape configuration, namely, fragmentation of primary forest and the composition of the surrounding forest m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 53 publications
2
111
1
3
Order By: Relevance
“…Due to their requirements for extensive home ranges, large frugivorous birds are especially extinction prone in small fragments (Renjifo, 1999;Uriarte et al, 2011). The ability to fly long distances allows large-bodied frugivores to connect habitat patches (Lees and Peres, 2009;Spiegel and Nathan, 2007).…”
Section: Box 5 Avian Frugivores and Seed Dispersal In A Fragmented Worldmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their requirements for extensive home ranges, large frugivorous birds are especially extinction prone in small fragments (Renjifo, 1999;Uriarte et al, 2011). The ability to fly long distances allows large-bodied frugivores to connect habitat patches (Lees and Peres, 2009;Spiegel and Nathan, 2007).…”
Section: Box 5 Avian Frugivores and Seed Dispersal In A Fragmented Worldmentioning
confidence: 99%
“…Sub-Andeans: Renjifo, 1999; Amazonia: Uriarte et al, 2011). The proportion of fruit in primate diets is positively correlated with home range size (Milton and May, 1976) and species persistence in forest fragments (Boyle and Smith, 2010).…”
Section: Mutualistic Plant-frugivore Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resultados similares foram obtidos por Stefanello et al (2009) em trecho de vegetação ciliar (Floresta Estacional Semidecidual), no meio e na foz do rio Pindaíba, em Mato Grosso, onde 85,7 e 77,5% das espécies desses ambientes não utilizam o vento como forma de propagação (zoocórica). Altas proporções de espécies zoocóricas presentes na chuva de sementes são indícios de ambientes conservados (TABARELLI;PERES, 2002;MELO et al, 2010;URIARTE et al, 2011).…”
Section: Discussionunclassified
“…The result indicated that the transmission efficiency of HPAI H5N1 among poultry was 1.7 times higher in regions where infected wild birds had been detected compared with regions without infected wild birds (Keawcharoen et al, 2011). In addition, waterfowl may transfer the virus mechanically during long distance migration, and feathers infected with HPAI H5N1 could also be a source of environmental contamination with high viral loads (Uriarte et al, 2011;Yamamoto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%